Fascinatie Textiel. - Laue, Dietmar; Pahnke-Felder, Ursula; Sterk, Beatrijs; Voragen, Thei (Venlo : Museum Van Bommel Van Dam, 1990)
van den Akker, Elizabeth ; Aslan, Nora ; Bossert, Birgit ; Dyrenforth, Noel ; Filliger-Nolte, Pia ; Grandt-Nielsen, Amy ; Heijnen, Sibyl ; Köhler, Renate ; Lorenz, Ingeborg ; Mailitis, Inese & Ivars ; Medel, Rebecca ; Newton, John E. ; Pahnke-Felder, Ursula ; Pock, Ingeborg ; Predominato, Lydia ; Ramirez, Carmen ; Rasmussen, Rolando ; Reese-Heim, Dorothea ; Speyer, Monika ; Stör, Katharina ; Takami, Harue ; Wilchins, Susan ; de Wolf, Lam
biografie
Fascinatie Textiel, Museum Van Bommel Van Dam, Venlo, van 18 mei tot en met 1 juli 1990
Nederlands & Engels & Duits
kunstcatalogus